NIKAH SIRRI DALAM PERBINCANGAN MEDIA MASA - Suryadilaga, Muhammad Alfatih (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
Sirri marriage is a growing phenomenon in society. The apparently large number ofÂ sirri marriages is due to widespread reporting by mass media, printed and electronic. As a part of religious teachings, marriage is a holy institution to humanize mankind. The purpose of marriage cannot be achieved if there is an effort to subvert its core values. One of the things which may reduce the essence of marriage is sirri marriage, as it is not recorded by the Office of Religious Affair and thus does not carry theÂ same legal force as official marriages. From the various cases of sirri marriages,Â most of them involve people in a public office and are economically well off, such as politicians, government officials and well off government and private employees. This means, that economic stability drives people to marry again to avoid sin, thus sirri marriage. On the flip side, poverty often coerces victims into sirri marriages. It seems that the reasons why people resort to sirri marriages include: prohibition to marry during civil service, the partner is not yet of age, polygamous civil servants fearful of superior reprimand and polygamous men fearful of their wives.